The Mobile Phone & Its Impact In Teenagers`Daily Life - Topalli, Bujane (European Scientific Journal, ESJ, 2016)
The mobile phone, as a medium has influenced the ways in which we can interact with other media. It is considered like a channel between traditional and new media. Its specific characteristics, social functions and also its uses may vary in different contexts and cultures. The mobile phone, has contributed in increasing the idea of personal media, and the emergence of new kinds of media behavior. According to Morley (2002), communication technologies transform and rearrange relations between the domestic and the public space. In particular, mobile communication functions to broaden the sphere of the home outside the physical household; to blur the boundaries between the public and private spheres. In this study we aim to discuss through the literature review the role of the phone in the everyday life, and to know more about the different ways and reasons why 12-15 year old teenagers, part of Municipality of Shkoder, use mobile phone. This qualitative research is based on semi structured interviews with children. The identified problems consist in: First: The children use more mobile phones in order to use the internet and social networks and this makes it really difficult for their parents to control them. This exposes more the children towards negative effect of internet usage. The second problem is that parents do not have enough knowledge on the usage of new technology. Third: Children have taken information about the risk of internet from the media or by friends and they haven’t discussed about this subject at school with teachers.